Sexualidade, parentalidade e doenças sexualmente transmissíveis/aids: análises em livros didáticos de ciências naturais - Silva, Clemilson Cavalcanti da (2015)
This study aimed to analyze how the concepts and methodological proposals about sexuality, parenting and sexually transmitted diseases / AIDS are addressed in two didactic collections of Natural Sciences of the final years of elementary school. Thus, it was used in this work a methodological approach of qualitative nature (MINAYO, 2008; LÜDKE and ANDRÉ, 2012). Regarding the method of assessment was applied to thematic content analysis (BARDIN, 2004; MINAYO, 2008) that works from categories and text dismemberment in context unit, registration unit, keywords and content considerations. Thus, the categories analyzed were: sexuality, parenting and STD / AIDS. The analysis was marked out from theoretical reference, among which we highlight: Foucault (2005, 2012, 2013); Castro, Abramovay and Silva (2004); Heilborn (1999, 2002, 2006); Altmann (2001, 2002, 2013); César (2004, 2009) Louro (2000, 2003, 2008); Taquette (2011, 2013); Among others. From the analysis of the categories in the teaching collections, we come to some considerations, we highlight: the most gained collection by teachers of Brazilian public schools has, according to MEC evaluators, and as our inferences, one Traditional bias, reductive, and in a few moments, with characteristics that may lead to biased impressions, especially in regards to sexual orientation. In addition, we didn't find, at any time, recent research quotes that addressed the analyzed categories. However, we realized that the author of this collection adhered the guidelines of the PCN, especially in the contents that address STD / AIDS issues. While, the second collection, which was less distributed and acquired by the cited teachers, brings, according to the MEC evaluation, a contemporary approach. In addition, it presents relevant quotes regarding the analyzed categories and were not found texts that refer to a prejudicial bias. However, we emphasize that, although there are quotes, they are relatively outdated research. In short, the findings of research and analysis given by MEC for both collections analyzed showed that teachers from public institutions have worked mostly with collections referring to traditional, reductionist and, sometimes, outdated content, which can lead to an impoverishment of the teaching of Natural Sciences.